Kisah Sukses Pengelolaan Keuangan Publik Islam: Perspektif Historis - Yuana Tri Utomo (Pusat Studi Ekonomi Islam Sekolah Tinggi Ekonomi Islam Hamfara, 2017)
This paper explains the history of Islamic public finance. Data is taken from journals, books and articles in the library. The reading of the data source by istiqrai with critically analyzed with historical phenomenologically approach is referring to the Prophet's era. The periode of management of Islamic public finance is threefold: prophet era, khulafaur rasyidun and umayyah abasiyyah, ottoman. In the prophetic periode, management of public finance was guided by al-Qur’an and Prophet SAW. The Prophet’s activity in managing public finance was due to his position as the founding of this system, for example is in the administration of baitulmal. During the khulafaur rasyidun: Abu Bakar, Umar, Utsman, Ali, management of public finance referred to al-Qur’an, sunnah and their ijtihad. At the Umar era, it was very prominent with the tafaadhul principle. The economic growth sped along with the expansion. In the umayyah, abasiyyah, utsmaniyyah periode each had features. The prominent Kholifah in Umayyah era was Umar Abdul Aziz managing public finance so well. There was difficult to find the poor recipients of zakat. The prominent kholifah in abassiyah was al-Ma’mun printing the dinnar. Kholifah in the Ottoman era was Sulaiman utilizing state’s property for the walfare of society.